Forecasting and modelling the rye market, as a niche grain crop, under conditions of increasing mineral fertiliser costs - Anatolii Dibrova; Viktoriia Baidala; Теtiana Mirzoieva; Ludmila Stepasyuk; Alla Chmil; Larysa Dibrova (Наукові горизонти)
The cultivation of rye as a niche crop is gaining increasing importance in Ukraine. However, the rising cost of mineral fertilisers necessitates forecasting and market modelling to mitigate risks and enhance the economic efficiency of production. This study aimed to assess the current state of supply and demand in the rye market, which is considered a niche grain crop, and to forecast the effects of changes in mineral fertiliser costs on key market parameters under probable scenarios. The research employed comparative analysis, tabular representation, statistical economic approaches, abstract-logical reasoning, and econometric modelling. In particular, the econometric partial equilibrium model AGMEMOD has been utilised. The potential of rye as a niche crop has been revealed, the current state of its production has been analysed, and the key factors influencing the formation of supply and demand in the Ukrainian rye market have been identified; the dynamics of the supply and demand balance in the rye market, taking into account various economic and other factors, have been analysed; a forecast has been made of the consequences of changes in the cost of mineral fertilisers on the main parameters of the development of the rye market in Ukraine under several probable scenarios. The forecast extended to 2026 and evaluated the effects of different changes on yields, sown areas, gross production, and the economic efficiency of rye cultivation. The research provided a foundation for improving the efficiency of decision-making and implementation of management strategies, contributing to the achievement of national agricultural policy objectives, including ensuring food security. The proposed methodological approaches and research findings may be valuable for public and sectoral authorities in developing priority measures aimed at enhancing the performance of the domestic grain sector